If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + 2) + -16 = 19 + 7 Reorder the terms: -6(2 + x) + -16 = 19 + 7 (2 * -6 + x * -6) + -16 = 19 + 7 (-12 + -6x) + -16 = 19 + 7 Reorder the terms: -12 + -16 + -6x = 19 + 7 Combine like terms: -12 + -16 = -28 -28 + -6x = 19 + 7 Combine like terms: 19 + 7 = 26 -28 + -6x = 26 Solving -28 + -6x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + -6x = 26 + 28 Combine like terms: -28 + 28 = 0 0 + -6x = 26 + 28 -6x = 26 + 28 Combine like terms: 26 + 28 = 54 -6x = 54 Divide each side by '-6'. x = -9 Simplifying x = -9
| 7k+19=5 | | 8x-2=6x+5 | | m=6n+8 | | x+x-.66=30 | | X^2-2/3=30 | | 9x^2-5x-1= | | 91=6(12+b) | | 25-x÷2=x/3 | | 5/42x=-6/42 | | 2b-3b= | | 5/42=-6/42 | | 9x-5=7x+29 | | -5(3x-4)= | | 25c^2+20ct+4t^2=0 | | 5x+6=3x+34 | | 48v^2-120v+75=0 | | 5x+7=3x+49 | | 2x+4x+60=180 | | 100c^2-120c+36=0 | | 6x-18=-126 | | (-1/3)2 | | 5x+60+10x=180 | | 8x+3=6y-8 | | 3(y-6)-5y=-8 | | 42sqrt(4*2/41xsqrt00.125*x | | 8y/2 | | 42sqrt(4*2/41xsqrt00.125 | | 6y-2=9+10y | | 12×10^7/4×10^4 | | 34=2(v+2)-8v | | cos(34)•20/x | | 5(y-2)/4=-4y |